UNDERSTANDING READING ENGLISH TEXT THROUGH STRATEGIES EMPLOYED BY STUDENTS AT UNIVERSITY OF PGRI PALEMBANG - Nyimas Nabila; Indawan Syahri; Asti Gumartifa (Journey: Journal of English Language and Pedagogy, 2023)
The goals of this study were to understand more about students' learning strategies for understanding English reading content and to discover why did students employed those strategies. Students in the second semester of the English Education Study Program at the University of PGRI Palembang participated in this research. A qualitative descriptive method was used in this study. A semi-structured interview was also used as a primary source of data. Data collection, data reduction, data display, and data verification were all utilized to examine the information. The data revealed that students used a variety of strategies to perceive the English reading text. Besides, habitual translation was the most commonly used reading strategy through students, while guessing the meaning of the text was the least commonly used reading strategy. Additionally, this study found through several reasons.